Effect of weather parameters on Alternaria leaf blight of isabgol (Plantago ovata) incited by Alternaria alternata - CHOUDHARY, ANAND; YADAV, ARJUN LAL; SINGH, JASVEER; CHOUDHARY, SUNITA (The Indian Journal of Agricultural Sciences, 2026)
Isabgol (Plantago ovata Forssk.) is a vital medicinal plant, highly valued for its substantial soluble fibre content and numerous health benefits. However, its cultivation is severely impacted by Alternaria leaf blight incited by Alternaria alternata, which affects both yield and quality. The present study was carried out during two winter (rabi) seasons of 2022–23 and 2023–24 at College of Agriculture, Swami Keshwanand Rajasthan Agricultural University, Bikaner, Rajasthan to investigate the effect of various weather parameters on the progression of Alternaria leaf blight of isabgol. Results indicated that the highest percent disease intensity (54.38%) occurred during 29 January–04 February meteorological week in 2022–23, while in 2023–24, the peak disease intensity (51.11%) was observed during the 05–11 February week. Correlation analysis revealed that maximum and minimum temperatures, rainfall, and sunshine hours were significantly negatively correlated with disease intensity, whereas maximum and minimum relative humidity and wind velocity showed a positive correlation with disease intensity for the 2022–23 season. These findings highlight the critical role of weather attributes in the infection process and spread of Alternaria leaf blight in isabgol, providing essential insights for effective disease management strategies.